Data files for Exploring the use of flow cytometry for understanding the efficacy of disinfection in chlorine contact tanks - Jarvis, Peter (Cranfield University, 2021)
Video files showing dispersion of tracer dependent on baffles.
Keywords: video content'; 'dispersion'; 'tracer'; 'bacteria'; 'disinfection'; 'Baffles'; 'Water Treatment Processes'